RNA-binding proteins as therapeutic targets in cancer - Jennifer Jungfleisch; Fátima Gebauer (RNA Biology)
RNA-binding proteins (RBPs) have emerged as critical regulators of cancer progression, influencing virtually all hallmarks of cancer. Their ability to modulate gene expression patterns that promote or inhibit tumorigenesis has positioned RBPs as promising targets for novel anti-cancer therapies. This mini-review summarizes the current state of RBP-targeted cancer treatments, focusing on five examples, eIF4F, FTO, SF3B1, RBM39 and nucleolin. We highlight the diversity of current targeting approaches and discuss ongoing challenges including the complexity of RBP regulatory networks, potential off-target effects and the need for more specific targeting methods. By assessing the future potential of novel therapeutic avenues, we provide insights into the evolving landscape of cancer treatment and the critical role RBPs may play in next-generation therapeutics.